An automatic alignment system for measuring optical path of transmissometer based on light beam scanning. Issue 9 (21st May 2018) - Zhou, Shudao; Ma, Zhongliang; Wang, Min; Peng, Shuling
Abstract: This paper proposes a novel alignment system based on the measurement of optical path using a light beam scanning mode in a transmissometer. The system controls both the probe beam and the receiving field of view while scanning in two vertical directions. The system then calculates the azimuth angle of the transmitter and the receiver to determine the precise alignment of the optical path. Experiments show that this method can determine the alignment angles in less than 10 min with errors smaller than 66 μrad in the azimuth. This system also features high collimation precision, process automation and simple installation.